Material Management System for the Waste Processing Industry at PT. Pallet with Economy Order Quantity (EOQ) Method - Bakhtiar, Mukhamad Yusuf; Misbah, Achmad (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
PT. Pallet is a waste processing company that uses plastic waste as the main material to make plastic pallet products. Based on initial observations, this company experienced problems in material management, thereby reducing cost-effectiveness and efficiency. The purpose of this study is to identify problems in material management and the procurement of raw materials for plastic waste used in the production process of making plastic pallets, as well as to find out some of the causal factors for the occurrence of deficiencies/excesses in the procurement of raw materials for production waste. This research uses a descriptive quantitative approach, and the researcher acts as a research instrument or data collector. The analytical method used is Economy Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP). The EOQ method has a lower total inventory cost. After calculating using the EOQ method, it is clear how much material must be ordered, the time to place the order and the total costs that must be incurred. The number of economic orders in the 3 months was 1,153.57 kg in October, 1,153.02 kg in November and 1,262.22 kg in December. The safety stock needed to expedite the production process is 394,345 kg in October, 376,306 kg in November and 99,652 kg in December. The results of the EOQ calculation produce a lower frequency of reorders, namely 203 times in one month, compared to the frequency of orders without EOQ, namely 378 times in one month.